Efforts to Improve Cooperative Management at the KOPJAS (Pious Charity Cooperative) Institution Based on Islamic Values - Rohmansyah, Rohmansyah; Fathurrahman, Ayif; Ahmadi, Ahmadi (UNIVERSITAS MUHAMMADIYAH MATARAM, 2026)
The problem faced by cooperatives is their poor service management, professionalism, and financial performance, which have not significantly impacted the existence of the cooperative and its members. Therefore, efforts are needed to improve knowledge about good cooperative management through community service in the form of training and mentoring. This community service aims to improve the management of the KOPJAS cooperative in managing its finances and services, so that it can progress and develop. The community service method used is a qualitative method with a training and mentoring model based on Islamic teachings. As a result, the management of the KOPJAS cooperative must be carried out professionally and responsibly in its services and finances, so that it can realize a cooperative that is advanced and developing in accordance with Islamic teachings. Many Quranic verses and Hadiths teach Islamic values, such as mutual assistance and helping those in need within a family. Through cooperatives, Islamic values can be applied in the form of excellent service management, financial management, and professionalism of management, in advancing the cooperative so that it can contribute more to society. The progress and development of cooperatives is evidenced by the establishment of charitable enterprises such as stalls, MSMEs, and others that support the increase in capital and profits of the cooperative and the welfare of its members and the community.